What is Orientation in Sinking?. Issue 3 (4th May 2019) - Juengel, Scott J.
ABSTRACT: In the wake of NASSR's 2018 conference theme—the Open—this essay attempts to think in open water by examining two literary accounts of dread and disorientation at sea. In Daniel Defoe's Robinson Crusoe (1719) and William Cowper's "The Castaway" (1799) we encounter the radical exposure of the subject to oceanic vastness with, as Crusoe laments, "no prospect … but perishing." Rather than read the episodes as instances of sublimity, I view them as meditations on the geometry of the event, their axes drawn in part by Immanuel Kant's philosophical writings on directionality, especially his "What is Orientation in Thinking?" (1786). As stories of forsaken sailors coordinate physical and metaphysical reduction, they also engage in an austere formal rigor—i.e., a body floating in space, a horizon line, a terminal verticality—that reminds us that form has always been orientation in thinking.